Analisis Kesulitan Pembelajaran Bahasa Arab pada Peserta Didik - Rojana, Eko (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The learning process often encounters obstacles that prevent the achievement of learning objectives. The same thing also applies to learning Arabic; there are many obstacles that can result in poor or fruitless learning. This can be caused by external or internal factors, and the possibilities are many. The aim of this research is to characterize the events currently occurring. This research uses a qualitative phenomenological method using interview guides, questionnaires and observation sheets with informants including the principal, teachers and class VII students at MTs Al-Mukarram who continue to experience difficulties learning Arabic. Students' inability to read the Koran and their inability to distinguish letters that are almost similar is a sign that they are still having difficulty learning the language and lack motivation. In learning Arabic, there is no such thing as a basic understanding. The importance of learning Arabic does not receive enough attention, and as learning progresses, boredom begins to appear. However, because most of the students, especially class VII MTs Al-Mukarram, are still beginners in the language, continued the Arabic language professor. to try to help students even though they still have difficulty mastering the language.